2011
DOI: 10.1021/jp203829z
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Multiphoton Dissociation Spectroscopy Study of Protonated p-Aminobenzoic Acid: Does Electrospray Ionization Afford the Amino- or Carboxy-Protonated Ion?

Abstract: Infrared multiphoton dissociation spectra of protonated p-aminobenzoic acid generated by electrospray ionization (ESI) from aqueous methanol and acetonitrile solutions were recorded in the gas phase from 2800-4000 cm(-1). The O-protonated ion is more stable than the N-protonated structure in the gas phase, whereas the opposite is true in both solutions. When CH(3)OH/H(2)O was used as the ESI solvent, only the O-protonated ion was observed. In contrast, a 70:30 mixture of the O- and N-protonated species were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
174
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(203 citation statements)
references
References 33 publications
27
174
2
Order By: Relevance
“…Interestingly, although the N-protonated form of 4-ABA•H + is the most stable tautomer in protic solution [63], the O-protonated structure is most stable when isolated in the gas-phase. Here, we calculate that O-protonated 4-ABA•H + is 5.6 kcal•mol -1 lower in energy than the N-protonated tautomer, which is in excellent agreement with earlier reported ranges of 4.1-9.5 kcal•mol -1 [54,55]. Interestingly, we find that adding a CH 3 OH molecule stabilizes the O-protonated structure relative to the N-protonated form by a further 3.3 kcal•mol -1 .…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Interestingly, although the N-protonated form of 4-ABA•H + is the most stable tautomer in protic solution [63], the O-protonated structure is most stable when isolated in the gas-phase. Here, we calculate that O-protonated 4-ABA•H + is 5.6 kcal•mol -1 lower in energy than the N-protonated tautomer, which is in excellent agreement with earlier reported ranges of 4.1-9.5 kcal•mol -1 [54,55]. Interestingly, we find that adding a CH 3 OH molecule stabilizes the O-protonated structure relative to the N-protonated form by a further 3.3 kcal•mol -1 .…”
Section: Resultssupporting
confidence: 92%
“…Earlier confirmation of these two tautomers was achieved by infrared multiple photon dissociation (IRMPD) spectroscopy [55], lowpressure HDX [54], and MS/MS [54,55]. [25,54,55]. It is interesting to note the observed shift in peak CV (particularly obvious for the CV = −1.5 V peak) as a function of water concentration.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Based on IM and MS/MS data, they conclude that these ions only differ in the site of protonation, and are thus referred to as "protomers". Other studies have reported on the observation of protomers for different analytes using both MS as well as other techniques such as gas-phase infrared photodissociation (IRPD) spectroscopy [56][57][58]. We also explain the observation here of two drift times for melphalan by the presence of charge isomers (protomers) in the gas phase [26].…”
Section: Observation Of Multiple Drift Times For Melphalansupporting
confidence: 58%
“…has been raised by Kass et al [19][20][21][22][23][24][25][26][27][28][29]. Generally, we know that protonation occurs predominantly on the most basic site of the molecule to generate the thermodynamically favored protonated ions in ESI.…”
Section: Introductionmentioning
confidence: 99%